Association Between Obstetric Risk Level and Psychomotor Development Impairments in Children Under Five Years - AdrianaEdit MinietCastillo; Jorge Luis Anaya-González; Jonathan E Muñoz Zambrano; Erlen Carmona Álvarez-Builla (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. Psychomotor development in early childhood is a key indicator of health and neurodevelopmental status. Perinatal risk factors can compromise this process, influencing the child's functional prognosis.  This study analyses the relationship between perinatal risk level and alteration of psychomotor development in children under 5 years of age, attended at the Caranqui Health Center of Ibarra in 2022.